Mucor and Aspergillus Maxillary Bone and Sinuses coinfection in a woman with Systemic Lupus Erythematosus: A Case Report - Hassan Mir Mohammad Sadeghi; Azin Kheradmand; Simin Dokht Shoaei (Novelty in Biomedicine)
Background: Mucorales and Aspergillus have invasive fungal infections with high mortality, mainly in immunocompromised and diabetic patients. The diagnosis is microbiological and pathological, with a strong clinical suspicion. The treatment is medical and surgical debridement. Invasive fungal coinfection by these two is reported as a case report. Here, we highlight the importance of considering the coinfection of Aspergillus and Mucor in the maxillary bone and paranasal sinuses in patients with systemic lupus erythematosus (SLE).